Dance in Sculpture of the Early 20th Century. Issue 4 (December 2019) - Portnova, Tatiana
This article is concerned with the ratio of plastic arts as exemplified by sculptural works depicting dances of the early 20 th century. Special attention is paid to the Greek motives in the Russian art of this period, which became the subject of inexhaustible aesthetic and artistic interest. The representation of ancient dance motifs, their figurative image and the nature of antiquity in sculptural plastics, various approaches to the interpretation of ancient plots and themes, the role and significance of the "antique" component in their artistic structure are considered in the article. The study of multi-level interactions between sculpture and dance in the context of antiquity calls for a comprehensive approach, including historical-cultural, theoretical-analytical and comparative-typological methods. Relating to ancient Greek images, ballet images of S. Konenkov, M. Ryndzyunskaya, N. Andreev, V. Vatagin, V. Beklimishev and S. Erzya provide a purely individual, unique and peculiar vision of dance corresponding to the ancient era. The categories and expressive means of dance were simultaneously analyzed close to the sculptural style of the masters because they are difficult to be divided methodologically and exist as an established artistic system. The concepts of "plastic expressiveness" in relation to the dancers imprinted in sculptures were interpreted. Analyzing the museum materials and sculptures depicting the dancing process, it was concluded that the ancient influence of plastic images on structural and genre determinants may vary.